Effect of thickness and shade of CAD/CAM composite on the light transmission from different light-curing units - Julia Dantas MAZÃO; Maria Tereza Hordones RIBEIRO; Stella Sueli Lourenço BRAGA; Karla ZANCOPÉ; Richard Bengt PRICE; Carlos José SOARES (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The thickness and shade of a restoration will affect the transmission of light from the light-curing unit (LCU). This study determined the power (mW), spectral radiant power (mW/nm), and beam profile of different LCUs through various thicknesses and shades of a CAD-CAM resin composite (BRAVA Block, FGM). Five thicknesses: 0.5; 0.75; 1.0; 1.5, and 2.0 mm, in three shades: Bleach; A2 and A3.5 of a CAD-CAM resin (n = 5). Two single-peak LCUs: EL, Elipar DeepCure-S (3M Oral Care); and OP, Optilight Max (Gnatus), and one multiple-peak LCU: VL, VALO Grand (Ultradent), were used. The LCUs were positioned touching the surface of the BRAVA Block. The power and emission spectrum were measured using a fiberoptic spectrometer attached to an integrating sphere, and the beam profiles using a laser beam profiler. The effect of the material thickness on the light attenuation coefficients was determined. VL and EL delivered more homogeneous beam profiles than OP. The type of the BRAVA Block had a significant effect on the transmitted power, and wavelengths of transmitted light (p < 0.001). There was an exponential reduction in the power and emission spectrum as the thickness of the BRAVA Block increased (p < 0.001). The light transmission through the A2 shade was least affected by the thickness (p < 0.001). The attenuation coefficient was higher for the violet light and higher for A3.5 than the A2 or Bleach shades. No violet light from the VL could be detected at the bottom of 2.0 mm of the BRAVA Block.